Narrative Transformation of “Nini Antéh” in Traditional and Modern Sundanese Literature - Nenden Sundari; Farid Rizqi Maulana; Susilawati Susilawati (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
Character of Nini Antéh is a significant figure in the Sundanese oral literary tradition who has undergone various transformations in modern literary. This study aims to analyze the narrative transformation of the Nini Antéh folktale into the modern drama script Antéh. This study focuses on comparing the intrinsic elements of both works, including characters, plot, setting, and theme. The study employed a qualitative method with a descriptive-analytical approach. The research data consisted of the Nini Antéh folktale as a representation of traditional literature and the Antéh drama script by Nunu Nazarudin Azhar as a representation of modern literature. The analysis was conducted using a structural approach to identify the elements that create the works, followed by a comparative literary approach to examine the similarities and differences between the two texts. The results show that both works share similarities in their main characters and central theme, namely the story of a woman who lives on the moon. Antéh is depicted in both works as loyal, patient, and skilled at borrowing or begging. However, there are differences in the plot development, setting, and conflict of the stories. The Nini Antéh folktale features a more detailed plot with social conflicts related to community life and the royal environment. In contrast, Antéh's play script emphasizes symbolic and psychological conflict with an imaginative and mythological setting. This difference demonstrates narrative transformation of folklore into modern drama. This transformation demonstrates how traditional stories can be adapted and developed to suit different aesthetic needs and cultural contexts.